Theoretical and experimental investigation on disc spring isolation system with loading rings. Issue 165 (February 2023) - Ma, Kaiqiang; Zhou, Ying; Lu, Decheng
Abstract: A novel disc spring isolation system (DSIS) design for buildings is proposed to isolate vibrations in the vertical direction. The system with nonlinear stiffness consists of disc springs and loading rings that reduce the influence of Coulomb friction between multiple disc springs. Theoretical analysis was first applied to establish a four-curve (FC) model to describe the force-displacement relation of DSIS by considering the influence of slip behavior and Coulomb friction between the loading rings and disc springs. Then, a series of vertical cyclic loading tests were carried out to study the different mechanical properties of DSIS with or without loading rings, and the effectiveness of the loading rings was verified. By comparing with the test results, the accuracy of the proposed FC model was verified. Then, the numerical solution method using the proposed FC model to solve the dynamic response of the single degree of freedom (SDOF) system was investigated. The nonlinear transfer function curves of DSIS with loading rings were compared with those of DSIS without loading rings by numerical analysis. Finally, the comparison study of SDOF for DSIS under the specific harmonic and train-induced vibration was carried out as a case study. The comparison shows that DSIS with loading rings more effectively reduces the start frequency of the isolated system, revealing the significant advantages of adopting DSIS with loading rings in vertical isolation. Highlights: A new disc spring isolation system(DSIS) with loading rings is proposed. A four curve(FC) model considering the influence of friction to describe force-displacement relationship of DSIS is proposed. DSIS is researched by experiments and the FC model is verified by test results. Dynamic analysis method using FC model for DSIS is proposed, and DSIS under train-induced vibration is studied.